Current and advancing treatments for metastatic colorectal cancer. (2nd January 2016) - Sanz-Garcia, Enrique; Grasselli, Julieta; Argiles, Guillem; Elez, M Elena; Tabernero, Josep
Abstract : Introduction : Colorectal cancer (CRC) is one of the leading causes of cancer deaths worldwide. Despite the introduction of several new drugs targeting the vascular endothelial growth factor or epidermal growth factor receptor (EGFR) signaling pathways, survival and disease control in metastatic CRC remains poor. Areas covered : Chemotherapy based on fluoropyrimidines and irinotecan or oxaliplatin has been the cornerstone of CRC standard of care for several decades. Optimal regimens are selected according to toxicity profiles and patient characteristics. The addition of targeted drugs inhibiting angiogenesis, notably bevacizumab, aflibercept and ramucirumab, has improved chemotherapy outcomes in metastatic CRC. Anti-EGFR agents, cetuximab and panitumumab, in combination with chemotherapy have also improved survival in patients with wild-type RAS tumors. In the refractory setting, there are emerging drugs such as regorafenib or TAS-102 that also have demonstrated impact on outcomes. Expert opinion : Drugs targeting signaling pathways involved in tumorigenesis improve patient outcomes over chemotherapy alone. Determining the most suitable combination and sequence should be carefully selected, with studies yet to provide a definitive solution to this unknown. Molecular mechanisms of colorectal cancer are at the forefront of research. Knowledge in this domain will help overcome resistance to therapies and introduce new drugs in the personalized CRC therapeutic scenario.